Hydrogen Diffusion and Its Effect on Hydrogen Embrittlement in DP Steels With Different Martensite Content - Wang, Zhen; Liu, Jing; Huang, Feng; Bi, Yun-jie; Zhang, Shi-qi (Frontiers in Materials, 2020)
The hydrogen diffusion behavior and hydrogen embrittlement susceptibility of dual phase (DP) steels with different martensite content were investigated using the slow strain-rate tensile test and hydrogen permeation measurement. Results showed that a logarithmic relationship was established between the hydrogen embrittlement index (IHE) and the effective hydrogen diffusion coefficient (Deff). When the martensite content is low, ferrite/martensite interface behaves as the main trap that captures the hydrogen atoms. Also, when the Deff decreases, IHE increases with increasing martensite content. However, when the martensite content reaches approximately 68.3%, the martensite grains start to form a continuous network, Deff reaches a plateau and IHE continues to increase. This is mainly related to the reduction of carbon content in martensite and the length of ferrite/martensite interface, which promotes the diffusion of hydrogen atoms in martensite and the aggregation of hydrogen atoms at the ferrite/martensite interface. Finally, a model describing the mechanism of microstructure-driven hydrogen diffusion with different martensite distribution was established.